Mengetahui Aturan Hukum dengan Menghafal Naskah Pembukaan UUD 1945 dan Pasal-Pasal UUD 1945 Secara Tekstual dan Mengetahui Makna yang Tekandung di Dalamnya Bagi Siswa-Siswi IPA-IPS SMA Negeri 7 Takengon - Seri Mughni Sulubara; Amrizal Amrizal; Bambang Eko Prayetno (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The rule of law is made to create order and security in society. The Preamble of the 1945 Constitution has legal certainty and expediency that regulates the life of society, nation and state in Indonesia. The 1945 Constitution is a written basic law that is binding both for the government, every state institution and is binding for every Indonesian citizen wherever he is and every resident in the territory of the Republic of Indonesia. The problem in this study is that there is still no socialization in the form of community service activities from Senior High School 7 Takengon students to memorize the textual opening of the 1945 Constitution and know the meaning contained therein. The purpose of this research is to provide motivation and ability so that students of Senior High School 7 Takengon are able to memorize the textual opening of the 1945 Constitution and know the meaning contained therein. After memorizing, remembering, it can be applied in everyday life as a student. The application is in the form of studying diligently, respecting parents and teachers, loving friends, and remaining guided by religious teachings. The method used is a survey method to identify and analyze problems related to the level of ability, understanding and knowledge of Senior High School 7 Takengon students towards the preamble of the 1945 Constitution and the articles of the 1945 Constitution. The results of the study showed that students of Senior High School 7 Takengon have enthusiasm and knowledge of the preamble of the 1945 Constitution and the articles of the 1945 Constitution.